Integration of Information for Patient Care: 2015 Redux - Rienhoff, O. (Yearbook of Medical Informatics, 2016)
Medical workstations are getting more and more powerful – however for the last decades they have been slow in making their way into the everyday life in medical care. In some resource rich organisations or smaller countries, their advance has gone further than elsewhere – however, a tipping point has not been reached. Again and again, new technologies and developments are pushing the need for integration of workstations into medical processes – currently the quantified self wave – however more options lead to more complexity and this growing complexity makes it more difficult to integrate the power of medical workstations in given culturally primed scenarios.
Keywords: Medical workstations; clinical decision support; electronic patient record; quantified self